Scientific and Methodological Approaches to the Study of Modern Russian-Language Poetry of Kazakhstan - Altayevna, Sabirova Dina (Journal of Cultural Analysis and Social Change, 2026)
Modern Russian-language literature is a unique phenomenon that combines the traditions of classical Russian literature with new artistic forms, challenges of globalization and the digital age. Despite its relatively young history, it has a significant impact on both Russian-language and world culture. The question of the need to study it in universities is relevant, since it affects important aspects of humanitarian education, critical thinking and cultural identity. This article will consider the reasons why modern Russian-language literature should be included in university curricula. Modern literature is a mirror of society. It records changes in the political, economic, social and cultural spheres, helping to better understand what is happening in the world. The study of modern literature at a university contributes to the development of analytical abilities and critical thinking skills. Unlike classical literature, the interpretation of modern prose and poetry is less straightforward, which encourages students to engage in deeper analytical work.